Epidemiological Aspects of Oral and Pharyngeal Cancer in Kerman Province, South Eastern Iran - G Chamani; MR Zarei; M Rad; M Hashemipoor; AA Haghdoost (Tehran University of Medical Sciences, 2009)
Background: Epidemiologic aspects of oral and pharyngeal cancers in Iran have not been studied adequately. We evaluated age-adjusted incidence rates by sex using pathological confirmed cases between 1991 and 2002 in Kerman Province, south eastern Iran. Methods: The information of cases was collected actively from all of the 18 histopathology departments around the province. The standardize risks were estimated using standard world population and the risk ratio for age and sex were estimated using negative binomial model. Results: The total number of newly diagnosed malignant oral and pharyngeal cancers was 334, represented 3.1% of all newly diagnosed cancers. The age-adjusted incidence rate for oropharyngeal cancers was 2.21 cases per 100 000 populations per year. The results suggested that those age 40 and over were 18.1 times more likely to develop oral and pharyngeal cancer than the younger group. The risk of developing oral and pharyngeal cancers was 1.75 times more common in males than females. Conclusion: This study showed that the overall incidence of oral and pharyngeal cancers in Kerman Province was lower than that in most parts of the world. The lower incidence might be due to behavioral differences such as low consumption of alcohol, chewing tobacco, and spicy foods.